Advanced small-bowel well-differentiated neuroendocrine tumours: An international survey of practice on 3rd-line treatment - Lamarca, Angela; Cives, Mauro; De Mestier, Louis; Crona, Joakim; Spada, Francesca; Oberg, Kjell; Pavel, Marianne Ellen; Alonso-Gordoa, Teresa (World Journal of Gastroenterology, 2021)
BACKGROUND Somatostatin analogues are an established first-line therapy for well differentiated small bowel neuroendocrine tumours (Wd-SBNETs), while and peptide receptor radionuclide therapy (PRRT) is frequently used as a second-line therapy. Adequate treatment selection of third-line treatment remains challenging due to the limited prospective data currently available on the best therapeutic sequence. AIM To understand current practice and rationale for decision-making by physicians in the 3rd-line setting by building an online survey. METHODS Weighted average (WA) of likelihood of usage between responders (1 very unlikely; 4 very likely) was used to reflect the relevance of factors explored. RESULTS Replies from representatives of 28 centers were received (5/8/2020-21/9/2020); medical oncologist (53.6%), gastroenterologist (17.9%); United Kingdom (21.4%), Spain (17.9%), Italy (14.3%). Majority from European Neuroendocrine Tumor Society (ENETS) Centres of Excellence (57.1%), who followed ENETS guidelines (82.1%). Generally speaking, 3rd-line treatment for Wd-SBNETs was: everolimus (EVE) (66.7%), PRRT (18.5%), liver embolization (LE) (7.4%) and interferon-alpha (IFN) (3.7%); chemotherapy (0%); decision was based on clinical trial data (59.3%), or personal experience (22.2%). EVE was most likely used if Ki-67 < 10% (WA 3.27/4) or age < 70 years (WA 3.23/4), in the 3rd-line setting (WA 3.23/4); regardless of presence/absence of carcinoid syndrome (CS), rate of progression or extent of disease. Chemotherapy was mainly utilised only if rapid progression (within 6 mo) (WA 3.35/4), Ki-67 10%-20% (WA 2.77/4), negative somatostatin receptor imaging (WA 2.65/4) or high tumour burden (WA 2.77/4); temozolomide or streptozocin was used with capecitabine or 5-fluorouracil (5-FU) (57.7%), FOLFOX (5-FU combined with oxaliplatin) (23.1%). LE was selected if presence of CS (WA 3.24/4) or Ki-67 < 10% (WA 2.8/4), after progression to other treatments (WA 2.8/4). IFN was rarely used (WA 1.3/4). CONCLUSION Everolimus was the most frequently used therapeutic option in the third-line setting. The most important factors for decision-making included Ki-67, rate of progression, functionality and tumour burden; since this decision is based on multiple factors, it highlights the need for a multidisciplinary assessment.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Advanced; Neuroendocrine tumour; Practice; Small bowel; Survey; Third-line